Scattering from an object behind multi-layer periodic gratings of cylindrical shapes - Kizilay, Ahmet; Saynak, Ugur; Uygur, Gokhan (TAYLOR & FRANCIS LTD, 2017)
The problem of electromagnetic scattering from a perfect electric conductor (PEC) object of arbitrary cross-section behind multilayer of periodic gratings of circular cylinders is solved by a hybrid method combining the Method of Moments (MoM), decomposition, and the Physical Optics methods. The periodic grating's periodic cell consists of multiple layers of lossy-dielectric scattering elements situated in free space. The PEC object under the periodic gratings assumed to be electrically large. A set of electric-field integral equations (EFIEs) for the perturbation currents both on the portion of the PEC object and the periodic gratings most strongly interacting with each other obtained using the surface equivalence principle and a decomposition method. Then, MoM is used to solve the EFIEs in the frequency domain to obtain the scattered electric field.
Keywords: Electromagnetic wave scattering; multilayered periodic structures; electric-field integral equations; physical optics; method of moments; MoM-PO hybrid; FREQUENCY-SELECTIVE SURFACES; ARBITRARY CROSS-SECTION; PLANE-WAVE SCATTERING; ELECTROMAGNETIC SCATTERING; DECOMPOSITION METHOD; CONDUCTING CYLINDER; LOSSY DIELECTRICS; MULTIPLE LAYERS; TM-SCATTERING; ARRAYS; Engineering; Physics